Fostering Sustainable Tourism in West Lampung: A Community Service Initiative Strengthening University–Local Government Collaboration - Feni Rosalia; Yuni Ratnasari; Maulana Agung Pratama; Suprihatin Ali; Dadang Karya Bakti; Rahayu Sulistiowati (CITAKARYA Jurnal Pengabdian Masyarakat, 2026)
West Lampung Regency possesses substantial ecotourism, geotourism, and cultural-tourism assets, yet their development is constrained by damaged road accessibility, persistent illegal levies, a tourism workforce with limited entrepreneurial readiness, and inadequate budget and supporting facilities. This community service initiative aimed to strengthen collaboration between Universitas Lampung and the local government in advancing sustainable tourism, taking the IDR 70 billion Lake Ranau Lumbok Seminung Thematic Tourism Market as its empirical anchor. The activity was carried out through a Focus Group Discussion (FGD) involving public servants of the Office of Cooperatives, Small and Medium Enterprises, Industry and Trade (Koperindag) of West Lampung and a multidisciplinary team of Universitas Lampung lecturers, organised in three stages: pre-activity preparation, the discussion itself, and post-activity evaluation. Four thematic streams were examined: the role of local government, sociological dimensions, community and start-up empowerment, and digital marketing support. The findings show that the local government has actively supported sustainable tourism through the development of creative-economy partners, particularly micro, small, and medium enterprises (MSMEs), and through emerging institutional coordination. Nevertheless, funding limitations, uneven community awareness, and infrastructure gaps remain salient barriers. The initiative confirms that multi-actor collaboration among universities, government, the private sector, and the media is a prerequisite for translating tourism potential into inclusive and resilient local development. The study recommends institutionalising participatory governance, embedding carrying-capacity assessment, and scaling digital promotion to increase visitor arrivals while safeguarding ecological and cultural integrity.